Investigating the Role of Glycerol as a Plasticizer in Durian Rind-derived Cellulose Bioplastic - Adikara, Andrew Benaldo; Abdillah, Khoirunnisa Budia; Shofinita, Dian; Wonoputri, Vita (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
The widespread use of conventional plastic packaging poses significant environmental challenges. As a sustainable alternative, bioplastics derived from cellulose sourced from agricultural waste are gaining interest. This study explores the development of biodegradable bioplastic films derived from durian rind cellulose, with glycerol used as a plasticizer. Cellulose was isolated from durian rind using chemical extraction methods, resulting in a 29% yield with 70.2% purity. Bioplastic films were synthesized by incorporating varying amounts of glycerol into the cellulose matrix. The successful integration of cellulose and glycerol were confirmed by Fourier Transform Infrared spectroscopy. Morphology analysis revealed that increasing glycerol disrupted the dense fiber structure, leading to more flexible and visually transparent films. This was consistent with colorimetric analysis, which showed increased transparency with higher glycerol concentrations. Glycerol addition also resulted in greater water vapor permeability and water absorption, attributed to the plasticizer’s hydrophilic nature. Biodegradability tests indicated that all bioplastic samples fully degraded within 10 days in soil, with faster degradation occurring at higher glycerol levels. In food packaging trials using sponge cake as a model, the bioplastic films effectively prevented mold growth over 10 days. However, moisture loss led to a reduction in water activity and an increase in product hardness. Conversely, samples wrapped in commercial polyethylene (PE) plastic retained moisture and texture but showed significant mold growth. These findings demonstrate the potential of durian rind cellulose as a sustainable raw material for biodegradable packaging, and highlight the critical role of glycerol concentration in tailoring film properties for food applications.